A desolation called peace - Martine, Arkady (Tor, 2021)
"An alien armada lurks on the edges of Teixcalaanli space. No one can communicate with it, no one can destroy it, and Fleet Captain Nine Hibiscus is running out of options. In a desperate attempt at diplomacy with the mysterious invaders, the fleet captain has sent for a diplomatic envoy. Now Mahit Dzmare and Three Seagrass--still reeling from the recent upheaval in the Empire--face the impossible task of trying to communicate with a hostile entity. Whether they succeed or fail could change the face of Teixcalaan forever"--